(3GdGYJHGQ aj GdfGSN hGdefShNs - (3eMeO Hf ehSi Hf YKeGf GHf MGRe, CHh HcQ, Rjf GdOjf, GdeYQha HGdMGRej,J (B584 (3g` s ((3OQG dMOjK GdCTQajI s)
(3ChdgG (B:s
(3Chdg fGbU hChd GdehLhO efg bHd (B( (3HGH ai eQhQ GdMeGQ bOGe GdeUdi (B) (3afGA GdcYHI , hCf GHf eSYhO gGL Edi CQV MHTI Ke QLY Edi ecI Ke gGLQ Edi GdeOjfI s
(3BNQgG (B:s
(3aEPG CWjY QShd Gddg Udi Gddg Ydjg hSde abO CWjY Gddg JYGdi HWGYI QShd Gddg Udi Gddg Ydjg hSde BNQ GdLRA GdQGHY hHJeGeg Je GdcJGH s
(3GdfSNI HgG MhGTs
(3ai CQHYI CLRAG MOjKIs
(3ai BNQ GdfSNI SeGY LeGYI ef GdYdeGA GdcJGH Ydi JGL GdOjf CHj eMeO YHOGddg Hf YeQ Hf Ydi GHf Mejg GdLhjfi SfI (B641(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs